AB0789 Vitamin D Deficiency and Disease Activity/Severity in Spondyloarthritis: Results of the ASAS-COMOSPA International Study. (9th June 2015) - Fernandes, S.; Etcheto, A.; van der Heijde, D.; Landewé, R.; van den Bosch, F.; Dougados, M.; Moltό, A.
Abstract : Background: Vitamin D deficiency has been associated with several chronic inflammatory diseases. However, only few studies have evaluated the vitamin D levels in spondyloarthritis (SpA) patients, with some controversial results. Objectives: a) To describe vitamin D status in a worldwide SpA population and b) to evaluate the association between vitamin D deficiency and demographic/geographic/season/SpA phenotype/disease activity and severity, and comorbidities. Methods: ASAS-COMOSPA is an international cross-sectional study, conducted in more than 15 countries representing the 4 continents. From a total of 3984 SpA patients included in the study, 1558 (39.1%) patients had available data on vitamin D level. Patients currently on vitamin D supplementation (528 patients) were excluded. The remaining 1030 SpA patients were included for this analysis. Demographics, patients' phenotype, disease activity/severity measures (ASDAS-CRP, BASDAI, 44 swollen/tender joint index, physicians' global assessment, hip articular replacement, bamboo spine) and SpA patient's comorbidities (cardiovascular disease, osteoporosis, cancer, infections) were assessed. Vitamin D deficiency was defined as <20 ng/ml (50 nmol/L). Statistical analysis: The mean ± SD of the available Vitamin D levels in the COMOSPA population and per country was calculated. Univariate and Multivariate analysis usinglogistic regression was performed to explain the variation in vitamin D deficiency in the COMOSPA cohort. Results: Mean vitamin D was 22.2 (±13.4) ng/ml, and vitamin D deficiency was observed in 527 (51.2%) patients. In the univariate analysis, patients with vitamin D deficiency had higher body mass index (26.3±5.3 vs. 25.7±5.3, p=0.0251); were more frequently living in Europe (55.5% vs. 44.5%; p=0.0037), and in latitudes above 37° (53.0%vs 47.0%, p<0.008), were dosed for Vitamin D levels in winter-spring (56.8%vs 43.2%; p<0.0001), presented more frequently with radiographic sacroiliitis (80.5% vs66.2%; p≤0.0001), and positive HLA B-27 (81.8% vs. 76.2%; p=0.0422). Patients with vitamin D deficiency had also higher meanASDAS-CRP (3.0±1.3 vs. 2.7±1.2; p=0.0015), BASDAI (3.9±2.3 vs. 3.5±2.3; p=0.0142), and there were more patients withhip articular replacement (22 vs. 6; p=0.0033). After adjusting for age, gender and variables with p<0.1 in the univariate analysis, vitamin D deficiency remained significantly associated with season winter/spring (odds ratio (OR)1.88 [95%CI=1.24; 2.85], p=0.0029) and radiographic sacroiliitis (OR2.07 [95%CI=1.29; 3.31], p=0.0026). No independent association between vitamin D deficiency and comorbidities in this worldwide SpA population was found. Conclusions: As expected, vitamin D deficiency primarily occurs during less sunny seasons of the year. Moreover, this study suggests that: 1) vitamin D deficiency in SpA is frequent worldwide and 2) such vitamin D deficiency might be associated with both disease activity and (potentially more importantly) disease severity. Acknowledgements: Study was conducted under the umbrella of ASAS and financially supported by unrestricted grants from Abbvie, Pfizer and UCB. Disclosure of Interest: None declared